A quantitative evaluation of deformable image registration based on MV cone beam CT images: Impact of deformation magnitudes and image modalities. (March 2020) - Huang, Yuliang; Li, Chenguang; Wang, Haiyang; Hu, Qiaoqiao; Wang, Ruoxi; Chang, Cheng; Ma, Wenjun; Li, Weibo; Wu, Hao; Zhang, Yibao
Highlights: Accuracy of DIR based on Halcyon MV CBCT was evaluated. Deformation magnitudes and imaging modalities influenced accuracy of DIR algorithm. DIR on Halcyon MVCBCT system might only be suitable in a limited range. Abstract: Background and purpose: To evaluate the impact of deformation magnitude and image modality on deformable-image-registration (DIR) accuracy using Halcyon megavoltage cone beam CT images (MVCBCT). Materials and methods: Planning CT images of an anthropomorphic Head phantom were aligned rigidly with MVCBCT and re-sampled to achieve the same resolution, denoted as pCT. MVCBCT was warped with twenty simulated pre-known virtual deformation fields (Ti, i = 1–20) with increasing deformation magnitudes, yielding warped CBCT (wCBCT). The pCT and MVCBCT were registered to wCBCT respectively (Multi-modality and Uni-modality DIR), generating deformation vector fields Vi and Vi ′ (i = 1–20). Vi and Vi ′ were compared with Ti respectively to assess the DIR accuracy geometrically. In addition, Vi, Ti, and Vi ′ were applied to pCT, generating deformed CT (dCTi ), ground-truth CT (Gi ) and deformed CT′ (dCTi ′) respectively. The Hounsfield Unit (HU) on these virtual CT images were also compared. Results: The mean errors of vector displacement increased with the deformation magnitude. For deformation magnitudes between 2.82 mm and 7.71 mm, the errors of uni-modality DIR were 1.16 mm ~ 1.73 mm smaller than that of multi-modality (p = 0.0001, Wilcoxon signed rank test). DIR could reduce the maximum signed and absolute HU deviations from 70.8 HU to 11.4 HU and 208 HU to 46.2 HU respectively. Conclusions: As deformation magnitude increases, DIR accuracy continues to deteriorate and uni-modality DIR consistently outperformed multi-modality DIR. DIR-based adaptive radiotherapy utilizing the noisy MVCBCT images is only conditionally applicable with caution.